2004
DOI: 10.1021/ja0359557
|View full text |Cite
|
Sign up to set email alerts
|

Water Molecule Adsorption on Protonated Dipeptides

Abstract: Equilibrium constants for the adsorption of the first water molecule on six protonated dipeptides (Gly-Gly+H(+), Gly-Ala+H(+), Ala-Gly+H(+), Ala-Ala+H(+), Pro-Gly+H(+), and Gly-Trp+H(+)) have been measured as a function of temperature, and DeltaH(o) and DeltaS(o) determined. Density functional theory calculations were performed for both the unsolvated peptides and the peptide water complexes at the B3LYP/6-311++G level. MP2/6-311++G** calculations were also carried out for Gly/Ala peptides. The calculations su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 58 publications
7
43
0
Order By: Relevance
“…[31] It should be noted that the second most stable [GA + H] + conformer lies 0.05 eV higher in electronic energy according to our calculations. These two bare ion structures correspond to the most stable structures found by Kohtani et al, [32] who explored the conformational space by means of molecular dynamics calculations followed by ab initio calculations. Their MP2 calculations [32] revealed that the structures are almost degenerate in electronic and free energies.…”
Section: A C H T U N G T R E N N U N G (Ch 3 Cn) and [Ga + H]supporting
confidence: 65%
“…[31] It should be noted that the second most stable [GA + H] + conformer lies 0.05 eV higher in electronic energy according to our calculations. These two bare ion structures correspond to the most stable structures found by Kohtani et al, [32] who explored the conformational space by means of molecular dynamics calculations followed by ab initio calculations. Their MP2 calculations [32] revealed that the structures are almost degenerate in electronic and free energies.…”
Section: A C H T U N G T R E N N U N G (Ch 3 Cn) and [Ga + H]supporting
confidence: 65%
“…[5][6][7][8][9] These systems also allow high-accuracy ab initio calculations and are often considered as model systems for the study of more complex structures. In addition, the amino acid alanine has attracted attention due to its radiation dosimetric properties and has been formally accepted as a secondary standard for high-dose and transfer dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…The basis set superposition error (BSSE) [23] correction is taken into account also with 6-311++G ** basis set to estimate the error levels for all these BEs. Hybrid density functional theory (DFT/B3LYP) [24] calculations on these complexes are carried out thoroughly because the hybrid method of DFT can give very similar structural parameters compared with MP2, and the density functional vibrational frequencies and intensities are in excellent agreement with the experimental data for glycine and other amino acid systems [25], and also because of its successful treatments on the protonated and metalated oligoglycine systems [2,4,10].…”
Section: Methodsmentioning
confidence: 99%
“…Thus tridentate, bidentate or monodentate complexes can be obtained depending on the different metal-ion sizes, valences, binding sites, and the conformational flexibility of the peptide [10].…”
Section: Series Of G 2 MX +/2+ /G 2 H + Mx +/2+mentioning
confidence: 99%
See 1 more Smart Citation